A DSS for the identification of forest land types by the Greek Forest Service. (2015) - Athanasiadis, Antonios; Andreopoulou, Zacharoula
The issue of land use and identification of land types is of great interest for the Greek Forest Service in order to avoid legal conflicts between the State and private landowners. The main decision problem is the interpretation of the law and the required objectivity during the process. This paper present a hypertext-oriented decision support system, based on hyperlinks and questionnaires, for the identification of forest land types. The interface was designed based on HTML programming language using the software Dreamweaver™ as several Java scripts were also employed to set the rules and treaties that hyperlinks must fulfil. Its purpose is to propose a methodology to achieve more objective and reliable decisions. Forest services and foresters-decision makers could use such a decision tool aiming at sustainable management in land use, as it can also assist in achieving an efficient administration which is a prerequisite for sustainable governance.